Joseph T. Freeman and Excellence in Rehabilitation Award Lecture. (17th December 2021) - Strotmeyer, Elsa
Abstract: The Joseph T. Freeman Award lecture will feature an address by the 2021 Freeman Award recipient Pamela Cacchione, PhD, CRNP, BC, FGSA, FAAN, of the University of Pennsylvania. The Joseph T. Freeman Award is a lectureship in geriatrics awarded to a prominent clinician in the field of aging, both in research and practice. The award was established in 1977 through a bequest from a patient's estate as a tribute to Dr. Joseph T. Freeman. The Excellence in Rehabilitation of Aging Persons Award lecture will feature an address by the 2021 Excellence in Rehabilitation Award recipient Gregory Hicks, MPT, PhD of the University of Delaware. The Excellence in Rehabilitation of Aging Persons Award is designed to acknowledge outstanding contributions in the field of the rehabilitation of aging individuals.